2009
DOI: 10.1103/physrevb.80.134403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a transport current on magnetic anisotropy in gyrotropic ferromagnets

Abstract: Current-induced torques are commonly used to manipulate non-collinear magnetization configurations. In this article we discuss current-induced torques present in a certain class of collinear magnetic systems, relating them to current-induced changes in magnetic anisotropy energy. We present a quantitative estimate of their characteristics in uniform strained ferromagnetic (Ga,Mn)As.PACS numbers:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
166
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 60 publications
9
166
0
Order By: Relevance
“…1 A similar calculation can be performed in the general case of coexisting Rashba and Dresselhaus SO interactions [17]. The effective fields corresponding to H SO of equations (2.1)-(2.3) are An alternative way to look at this phenomenon has been introduced by Garate & MacDonald [71] by calculating the change in magnetocrystalline anisotropy energy induced by the flow of a steady-state electric current in a noncentrosymmetric FM conductor. This follows from the general definition of the internal anisotropy field of an FM as the derivative of the ground-state energy with respect to the direction of the magnetization, analogously to the derivation of the effective magnetic field that enters into the Landau-Lifshitz equation of magnetization dynamics.…”
Section: Current-induced Spin-orbit Torques (A) Combined Effects Of Ementioning
confidence: 99%
“…1 A similar calculation can be performed in the general case of coexisting Rashba and Dresselhaus SO interactions [17]. The effective fields corresponding to H SO of equations (2.1)-(2.3) are An alternative way to look at this phenomenon has been introduced by Garate & MacDonald [71] by calculating the change in magnetocrystalline anisotropy energy induced by the flow of a steady-state electric current in a noncentrosymmetric FM conductor. This follows from the general definition of the internal anisotropy field of an FM as the derivative of the ground-state energy with respect to the direction of the magnetization, analogously to the derivation of the effective magnetic field that enters into the Landau-Lifshitz equation of magnetization dynamics.…”
Section: Current-induced Spin-orbit Torques (A) Combined Effects Of Ementioning
confidence: 99%
“…1a). However, when carriers experience both the spin-orbit coupling and magnetic exchange coupling, the inversion asymmetry can generate a non-equilibrium spin density component of extrinsic, scattering-related 22,23 or intrinsic Berrycurvature [24][25][26] origin, which is magnetization dependent and yields an antidamping-like torque BM Â (M Â f). Experiments in (Ga,Mn)As confirmed the presence of the ISGE-based mechanism 8,17,18 and demonstrated that the field-like and the Berry-curvature antidamping-like SOT components can have comparable magnitudes 25 .…”
mentioning
confidence: 99%
“…2,3 Beside the conventional spin-transfer torque, the concept of spin-orbit torque in both metallic systems and diluted magnetic semiconductors (DMS) has been studied theoretically and experimentally. [4][5][6][7][8][9] In the presence of a charge current, the spin-orbit coupling produces an effective magnetic field which generates a nonequilibrium spin density that, in turn, exerts a torque on the magnetization. [4][5][6] Several experiments on magnetization switching in strained (Ga,Mn)As have provided strong indications that such a torque can be induced by a Dresselhaus-type spinorbit coupling, achieving critical switching currents as low as 10 6 A/cm 2 .…”
mentioning
confidence: 99%
“…The bulk inversion asymmetry allows us to augment the KohnLuttinger Hamiltonian by a strain-induced spin-orbit coupling of the Dresselhaus type. 5,7 We assume the growth direction of (Ga,Mn)As is directed along the z-axis; two easy axes are pointed at x and y, respectively. 10 In this case, the components of the strain tensor xx and yy are identical.…”
mentioning
confidence: 99%